LEARNING TO WRITE INSTRUCTIONS: IMPLEMENTATION OF 21st CENTURY LIFE SKILLS INNOVATION - Yohanis Hukubun; Iwan Rumalean; Everhard M Solissa (JURNAL TAHURI, 2022)
This paper aimed to describe learning to write as part of 21st century life skills. Writing as basic literacy is the main material in the 2013 curriculum. One type of writing is writing instructions which require the abilities and skills acquired from educational institutions to be applied in everyday life. Writing instructions is one of the four language skills should be mastered by students. Therefore, Indonesian language teachers are required to master the material for writing instructions both theoretically and practically. Theoretically, it explained about the meaning of writing, types of writing, writing instructions. Practically, they were implemented in learning according to Regulations of the Minister of Education and Culture Number 22 of 2016 and Number 103 of 2014 concerning on standard process. In those regulations, it is explained about graduate competency standards, syllabus, and lesson plan. The first step that needs to be done before preparing the lesson plan is to analyze the graduate competence standard (GCS). After analyzing the GCS, it is then translated into a syllabus. Furthermore, the writing of lesson plans developed from the syllabus to be a direction of learning in achieving basic competencies. This paper was the result of the collaboration of the community service group of Faculty of Teacher Training and Education of Unpatti in South Buru Regency in 2021